Transport & fate of chemicals in soils principles & applications - Selim, H. Magdi 1944- (Advances in trace elements in the environment, 2014)
"This book provides the fundamentals for the understanding of reactive chemicals retention and their transport in soils and aquifers. The book offers the first comprehensive treatment with supporting examples of mathematical models that describe contaminants reactivity and transport in soils and aquifers. It is also a practical guide for designing experiments and collecting data that focuses on characterizing retention as well as release kinetic reactions in soils and contaminant transport experiments in the laboratory, greenhouse (column) and in the field."--